Injuries Type and its Relation with Glasgow Coma Scale, Injury Severity Score and Blood Transfusion in Road Traffic Accident Victims - aldosari, khalid hadi (Medicni Perspektivi, 2019)
Background: Motor Vehicular Accidents claim about 1.2 million lives and injure more than 10 million people annually worldwide. The injuries caused by MVAs can be analyzed based on the type of injury, injury severity score, Glasgow Coma Scale and required blood transfusion. Methodology: A total number of 190 patients were included in this retrospective study from January 01, 2010 to December 31, 2015. The study aimed to determine the correlation between the type of injuries and GCS, ISS, and blood transfusions in the patients suffering from Motor Vehicle Accidents, who were presented to the Emergency Department at the King Khalid Hospital. All the data of the patients fulfilling the inclusion criteria were collected from the database at medical records department of the hospital. Results: Majority of the patients were adults Saudi male. 68.9% of the patients did not sustain shock, and 75.8% of patients did not require a blood transfusion. Patients with head, neck, chest, abdominal, internal organ, pelvic or spinal injuries conferred a statistically significant higher mean ISS. Patients with abdominal or internal organ injuries had a statistically significant higher mean units of blood transfused. GCS was seen to be lower in the head, neck, chest, abdominal, internal organ, spinal and other injuries. Conclusions: The study documents a significant correlation between the type of injury and GCS, ISS, and blood transfusion in victims of road traffic accident. Emergency physician and the caregivers should be more careful about the injuries associated with lower GCS. Patients sustaining injuries of certain parts related to high ISS (i.e., head, chest, abdominal, internal organ, pelvic) should be addressed on priority basis.